The Multimedia revolution [videorecording] today & tomorrow - Hoff, Lisa; Nielson, Jeff; Reeder, Rich (Multimedia Technology, 1995)
Reviews some of the best applications of multimedia technology today as well as takes a look at the delivery of multimedia beyond CD-ROM including interactive television, bulletin board systems and the Internet. Describes the potential health risk of computer work, alternate methods for distributing multimedia programs, new types of two-way interactivity and visualize new ways to use multimedia technology.